การวิเคราะห์ต้นทุนและผลประโยชน์ทางเศรษฐศาสตร์ ของโครงการศูนย์ออกกำลังกาย ของมหาวิทยาลัยพายัพ - สรวุฒิ บุญญพิทักษ์สกุล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objectives of this study were to analyze the cost-benefit of exercise gymnasium project of Payap University, and to investigate the financial-economic feasibility and sensitivity analysis of the project. Net present value (NPV), Benefit-Cost ratio (B/C ratio), Interest rate of return (IRR) and Payback period (PP) were employed for the feasibility analysis. Regarding to the economic feasibility analysis, the results indicated the NPV was 515,618 bath, B/C ratio is 1.14, IRR was 19.15% and PP was 8.09 years. The sensitivity analysis were performed by simulating the maximum changes of cost and minimum changes of benefit whereas the internal rate of return (IRR) approach to the discount rate of the project. According to the economic study the cost could be changed as maximum rate of 13.75% and the benefit could be changed as minimum rate of 12.1%. It implied this project highly demonstrated the possibility and valuable of the investment. Therefore, policymaker should strongly implement measures to support this project to be existed.